General, but not myeloid or type II lung epithelial cell, myeloid differentiation factor 88 deficiency abrogates house dust mite induced allergic lung inflammation. (13th October 2016) - Anas, A. A.; Yang, J.; Daan de Boer, J.; Roelofs, J. J. T. H.; Hou, B.; de Vos, A. F.; van der Poll, T.
Summary: Asthma is a highly prevalent chronic allergic inflammatory disease of the airways affecting people worldwide. House dust mite (HDM) is the most common allergen implicated in human allergic asthma. HDM‐induced allergic responses are thought to depend upon activation of pathways involving Toll‐like receptors and their adaptor protein myeloid differentiation factor 88 (MyD88). We sought here to determine the role of MyD88 in myeloid and type II lung epithelial cells in the development of asthma‐like allergic disease using a mouse model. Repeated exposure to HDM caused allergic responses in control mice characterized by influx of eosinophils into the bronchoalveolar space and lung tissue, lung pathology and mucus production and protein leak into bronchoalveolar lavage fluid. All these responses were abrogated in mice with a general deficiency of MyD88 but unaltered in mice with MyD88 deficiency, specifically in myeloid or type II lung epithelial cells. We conclude that cells other than myeloid or type II lung epithelial cells are responsible for MyD88‐dependent HDM‐induced allergic airway inflammation. Abstract : The TLR adaptor protein MyD88 is important for HDM induced asthma, as allergic responses are abrogated in mice with general deficiency of MyD88. Cells other than myeloid or type II lung epithelial cells however are responsible for MyD88 dependent HDM induced allergic airway inflammation.